Myosin XI-Dependent Formation of Tubular Structures from Endoplasmic Reticulum Isolated from Tobacco Cultured BY-2 Cells - Etsuo Yokota; Haruko Ueda; Kohsuke Hashimoto; Hidefumi Orii; Tomoo Shimada; Ikuko Hara‐Nishimura; Teruo Shimmen (2011)
Abstract The reticular network of the endoplasmic reticulum (ER) consists of tubular and lamellar elements and is arranged in the cortical region of plant cells. This network constantly shows shape change and remodeling motion. Tubular ER structures were formed when GTP was added to the ER vesicles isolated from tobacco (Nicotiana tabacum) cultured BY-2 cells expressing ER-localized green fluorescent protein. The hydrolysis of GTP during ER tubule formation was higher than that under conditions in which ER tubule formation was not induced. Furthermore, a shearing force, such as the flow of liquid, was needed for the elongation/extension of the ER tubule. The shearing force was assumed to correspond to the force generated by the actomyosin system in vivo. To confirm this hypothesis, the S12 fraction was prepared, which contained both cytosol and microsome fractions, including two classes of myosins, XI (175-kD myosin) and VIII (BY-2 myosin VIII-1), and ER-localized green fluorescent protein vesicles. The ER tubules and their mesh-like structures were arranged in the S12 fraction efficiently by the addition of ATP, GTP, and exogenous filamentous actin. The tubule formation was significantly inhibited by the depletion of 175-kD myosin from the S12 fraction but not BY-2 myosin VIII-1. Furthermore, a recombinant carboxyl-terminal tail region of 175-kD myosin also suppressed ER tubule formation. The tips of tubules moved along filamentous actin during tubule elongation. These results indicated that the motive force generated by the actomyosin system contributes to the formation of ER tubules, suggesting that myosin XI is responsible not only for the transport of ER in cytoplasm but also for the reticular organization of cortical ER.